Generalized Momentum Operator - Izadparast, Masoumeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In this research, we propose a generalized momentum operator upon imposing the spatial expansion provided that the EUP relation is confirmed. According to the EUP algebra, we use A(x) to be an auxiliary function ( or 1+ µ (x)) in the construction of our new momentum. Thus, we provide a formalism containing the auxiliary function in the real or complex domain upon which one has the freedom to define a hermitian or non-hermitian momentum operator. We start with introducing a generalized Lagrangian density affected by the proposed formalism. Our investigation is continued on the motion of a quantum particle under the variation of such Lagrangian density. Besides, we demonstrate the PT -symmetry field theory including the Ψ(x,t), Ψ∗ (x,t) or ΨPT (x,t) in the structure of the extended Lagrangian density. Having applied the principle of least action, the Euler-Lagrange equations lead to the corresponding Schrödinger equations. Upon finding the generalized Lagrangian density, we obtain the Hamiltonian density, momentum density and energy flux which are known to be the elements of the stress-energy tensor. The expectation value of the generalized Hamiltonian density for the hermitian and PT -symmetric fields are determined where it leads to the energy of the system. Thereupon, we extend the probability and particle current densities which significantly satisfy the continuity equation. Next, we develop further the concept of generalized momentum operator and elucidate the significance of our proposal considering once the real definition and once the PT -symmetric structure. With solving the eigen-value problems for the two combinations, we represent the eigen-values and eigen-functions of some examples of the generalized momentum operator. In accordance with the generalized Schrödinger equation, the kinetic energy operator is rebuilt and consequently the Hamiltonian operator is identified based on the imposed potential energy and the new kinetic energy. The corresponding differential equations are declared and the exact solutions are computed using the variable transformation method. Accordingly, we transform the extended Schrödinger equation from x-space into the target space, here z-space, with the manner whose energy spectrum remains identical. Later, we demonstrate an illustrative examples based on the idea of a step momentum operator which is flexible to have a hermitian or the PT -symmetric Hamiltonian operator. We employ the formalism such that expresses a sudden change in the momentum of a system at a specific point. To show that, we use a step auxiliary function and develop the Schrödinger equation considering a quantum particle inside a square well. The outcomes yield infinite bound states with real energy spectrum for the particles with hermitian step momentum, it is finite for a particle with PT -symmetric momentum. Afterwards, we study the PT -symmetric Hamiltonian in two dimensions. Having considered standard kinetic energy, a two dimensional complex harmonic oscillator potential is introduced which is invariant under the parity and time reversal operator. The Schrödinger equation yields real eigen-values with complex eigen-functions. We also construct the coherent state of the system by using a superposition of 12 eigen-functions. Utilizing the complex correspondence principle for the probability density, we investigate the possible modifications in the probability densities due to the non-hermitian aspect of the Hamiltonian.

ÖZ: Bu ara¸stırmada, EUP ili¸skisinin dogrulanması ko¸suluyla, mekansal geni¸slemeyi ˘ dayatarak genelle¸stirilmi¸s bir momentum operatörü öneriyoruz. EUP cebrine göre, yeni momentumumuzun in¸sasında yardımcı fonksiyon ( veya 1 + µ (x)) olarak A(x) kullanıyoruz. Böylece, bir hermityen veya hermityen olmayan momentum operatörü tanımlama özgürlügüne sahip olan gerçek veya karma¸sık alandaki yardımcı ˘ fonksiyonu içeren bir formalizm saglıyoruz. Önerilen formalizmden etkilenen ˘ genelle¸stirilmi¸s bir Lagrange yogunlu ˘ gu tanıtarak ba¸slıyoruz.Ara¸stırmamız, böyle bir ˘ Lagrange yogunlu ˘ gunun de ˘ gi¸simi altında bir kuantum parçacı ˘ gının hareketi üzerinde ˘ devam ediyor.Ayrıca, a¸sagıdakileri içeren ˘ PT -simetri alan teorisini gösteriyoruz: Ψ(x,t), Ψ∗ (x,t) or ΨPT (x,t) geni¸sletilmi¸s Lagrange yogunlu ˘ gunun yapısında. En ˘ az etki ilkesini uygulayan Euler-Lagrange denklemleri, kar¸sılık gelen Schrödinger denklemlerine yol açar. Genelle¸stirilmi¸s Lagrange yogunlu ˘ gunu bulduktan sonra, ˘ gerilim-enerji tensörünün elemanları olarak bilinen Hamilton yogunlu ˘ gu, momentum ˘ yogunlu ˘ gu ve enerji akı¸sını elde ederiz. Hermitian ve ˘ PT -simetrik alanlar için genelle¸stirilmi¸s Hamiltonian yogunlu ˘ gunun beklenen de ˘ geri, sistemin enerjisine ˘ götürdügü yerde belirlenir. Bunun üzerine, süreklilik denklemini önemli ölçüde ˘ saglayan olasılık ve parçacık akım yo ˘ gunluklarını geni¸sletiyoruz. Daha sonra, ˘ genelle¸stirilmi¸s momentum operatörü kavramını daha da geli¸stirecegiz ve bir kez ˘ gerçek tanım ve bir kez de PT -simetrik yapıyı göz önünde bulundurarak teklifimizin önemini açıklayacagız. ˘ ˙Iki kombinasyon için öz deger problemlerini ˘ çözerek, genelle¸stirilmi¸s momentum operatörünün bazı örneklerinin öz degerlerini ve ˘ öz fonksiyonlarını temsil ediyoruz. Genelle¸stirilmi¸s Schrödinger denklemine göre, kinetik enerji operatörü yeniden olu¸sturup, uygulanan potansiyel enerjiye ve yeni kinetik enerjiye dayalı olarak Hamilton operatörü tanımlıyoruz. Kar¸sılık gelen diferansiyel denklemler bildirilir ve kesin çözümler degi¸sken dönü¸stürme yöntemi ˘ kullanılarak hesaplanır. Buna göre, geni¸sletilmi¸s Schrödinger denklemini x-space’den hedef uzaya, burada z-space’e, enerji spektrumu aynı kalacak ¸sekilde dönü¸stürüyoruz. Daha sonra, bir hermitiyen veya PT -simetrik Hamilton operatörüne sahip olmak için esnek olan bir adım momentum operatörü fikrine dayanan açıklayıcı bir örnek gösterecegiz. Belirli bir noktada sistemin momentumundaki ani bir de ˘ gi¸sikli ˘ gi ifade ˘ eden formalizmi kullanacagız. Bunu göstermek için, bir adım yardımcı fonksiyonu ˘ kullanıyoruz ve kare bir kuyu içindeki bir kuantum parçacıgını dikkate alarak ˘ Schrödinger denklemini geli¸stiriyoruz. Sonuçlar, hermit adım momentumlu parçacıklar için gerçek enerji spektrumlu sonsuz baglı durumlar verir, ˘ PT -simetrik momentumlu bir parçacık için sonludur. Daha sonra, PT -simetrik Hamiltoniyeni iki boyutta inceleyecegiz. Standart kinetik enerji göz önüne alındı ˘ gında, parite ve zaman ˘ ters çevirme operatörü altında degi¸smez olan iki boyutlu karma¸sık harmonik osilatör ˘ potansiyelini tanıtacagız. Schrödinger denklemi, karma¸sık öz fonksiyonlara sahip ˘ gerçek öz degerleri verir. Ayrıca 12 öz fonksiyonun üst üste binmesini kullanarak ˘ sistemin tutarlı durumunu da olu¸sturacagız. Yo ˘ gunluk olasılı ˘ gı için karma¸sık yazı¸sma ˘ ilkesini kullanıp Hamiltonian’ın hermityen olmayan yönü nedeniyle olasılık yogunluklarındaki olası de ˘ gi¸siklikleri ara¸stıraca ˘ gız.
Doctor of Philosophy in Physics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2021. Supervisor: Prof. Dr. S. Habib Mazharimousavi.
Keywords: Physics Department; Quantum theory--Quantum Mechanics--Physics; Exact-Solution, Non-Hermitain Quantum Physics, Generalized Lagrangian, PT -Symmetry, Non-Hermitian Field Theory